Optimization of Production Control Based on Green Metrics to Reduce Production Emissions and Waste: A Multi-Objective Approach in the Wood-Processing Manufacturing Industry - Dharma Widada; Masayu Widiastuti (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
The manufacturing industry is a dominant contributor to global greenhouse gas emissions and industrial solid waste, necessitating a paradigm shift from output-centric to sustainability-integrated production management. This study develops and validates a multi-objective production control optimization model that embeds green metrics as core performance dimensions within the production decision-making framework of a wood-processing company in Kalimantan, Indonesia. The model integrates three simultaneous objective functions—minimizing CO₂-equivalent emissions, minimizing solid waste generation, and maximizing production output—subject to 18 operational, environmental, and regulatory constraints and governed by 28 decision variables. Green metrics dimensions were prioritized through the Analytical Hierarchy Process (AHP), yielding weights of 0.342 (greenhouse gas emissions), 0.261 (solid waste management), 0.198 (energy efficiency), 0.124 (water consumption), and 0.075 (material toxicity), with a Consistency Ratio of 0.043, confirming reliable expert judgment. Environmental waste streams were identified using the Green Value Stream Mapping (G-VSM) method, revealing four previously undetected waste categories including volatile organic compound (VOC) emissions and unrecovered wood-dust biomass. Model validation against three months of historical production data demonstrated a prediction accuracy of 94.7%, with parametric stability maintained at ±15% variation. Following six months of staged implementation (January–June 2024), CO₂eq emissions declined by 28.6% (from 4,782 to 3,412.8 ton/yr), solid waste decreased by 34.2% (from 1,467.4 to 965.8 ton/yr), and energy consumption fell by 22.4% (from 7,518.3 to 5,831.0 MWh/yr)—all exceeding predetermined targets. Simultaneously, production output increased by 18.3% and operating costs decreased by 15.7%. Emission intensity was reduced from 76.6 to 46.2 kg CO₂eq/m³, placing the company below the Southeast Asian industry benchmark of 58.3 kg CO₂eq/m³ (UNIDO, 2023). Financial analysis indicates a payback period of 7.4 months and a Net Present Value of IDR 18.9 billion over five years. These findings affirm that green metrics-integrated production control delivers simultaneous environmental and economic performance improvements, offering a replicable framework for sustainable manufacturing transformation.